Farce, satire et science dans The Emperor of the Moon (1687) d’Aphra Behn - Florence March (Etudes Epistémè)
As suggested by its title, The Emperor of the Moon : A Farce (1687) by Aphra Behn consists of a satirical staging of the New Astronomy and, on a wider scale, of experimental science, even though, by a process of contamination, astrology, alchemy and Rosicrucianism are also inevitably targeted. Although the subject-matter is far from new, Behn deals with it in an entirely original way. Thus the play is not so much characterized by the staging of scientific phenomena as by the dramatist’s exploitation of the codes and methods common to farce, satire and the so-called New Science. I will attempt to show how the close interweaving of the generic, satirical and scientific codes results in a new, stimulating staging of the satire of science. Three main strategies prove of particular interest, as they underlie the whole play and closely connect form and content, thus providing a structuring function : the ever-increasing use of the spectacular dimension, the significance of observation, and eventually, the levelling-down strategy.